A high static performance hierarchical three-dimensional shifted completely connected network - Ali, Mohammed N. M.; Rahman, M. M. Hafizur; Abubakar, Adamu; Al-Naeem, Mohammed; Hossain, Eklas (Institute of Electrical and Electronics Engineers, 2022)
In recent years, there has been a significant shift toward the adoption of the ‘‘Internet of Things (IoT)’’ era, in which vast amounts of data are collected and processed, and Artificial intelligence (AI) is used to make critical choices. When acting in real-time, it is vital to use devices with a lot of computing power. MPC (Massively Parallel Computer) Two-dimensional (2D) design systems are the most powerful computers available. Unfortunately, they can’t meet the need for the advanced computing operation required by many applications. As a result, it is critical to invest in developing high operational capacity systems that will meet the current computational power consumption demands. This paper developed the architecture of the two-dimensional Shifted Completely Connected Network (2D-SCCN) and proposed a three-dimensional (3D) network to achieve greater capacity and performance. The shortest path protocol on three-dimensional Shifted Completely Connected Network (3D- SCCN) was established, tested by computer simulator, and compared based on ‘‘shortest diameter’’, ‘‘shortest average distance’’, ‘‘lowest cost’’, ‘‘moderate bisection width’’, and ‘‘high arc-connectivity’’ among other characteristics. As a result, ‘‘3D-SCCN’’ was the most efficient method of transmitting a message between two nodes, increasing the system’s real-time response capability.